A gift from Bob [videorecording (DVD)] - Smith, Charles Martin; Treadaway, Luke, 1984-; Wilson-Jones, Anna; Tonteri-Young, Kristina; Bowen, James, 1979-; Bowen, James, 1979- (Lionsgate, 2021)
Street musician James Bowen and his beloved cat Bob spend their final Christmas on the street together.